منهج أبي الفضل الحريري في الاحتجاج للقراءات من خلال كتابه "الشفاء في علل القراءات" - مداح أبو بكر الصديق; عواد حمزة (University of Eloued جامعة الوادي, 2023)
يتناول هذا البحث دراسة منهج أبي الفضل الحريري في الاحتجاج للقراءات في كتابه "الشفاء في علل القراءات"؛ وذلك من خلال تتبع توجيهاته في هذا الكتاب؛ للوقوف على الأسس التي استند إليها في إيضاح عِلل القراءات، ابتُدِئَ البحث بمقدّمة للتعريف بالموضوع وأهميته، ثم ترجمة لأبي الفضل الحريري، ثم دراسة منهجه في الاحتجاج للقراءات. وأكّد هذا البحث على أنّ قراءات الصحابة وخطّ المصحف، إضافة إلى كلام العرب ولهجاتها؛ من أبرز الأسس التي استند إليها أبو الفضل الحريري في الاحتجاج للقراءات، وأكّد البحث أيضا على أنّ حُجَج أبي الفضل الحريري في إيضاح علل القراءات كانت موافقة لتوجيهات القراء والمفسرين. This research addresses the study of Abu Al-Fadl Al-Hariri's methodology in providing evidence for the readings in his book "Al-Shifa' in the evidences of al-Qira'at"; This is done by following his explanations in this book to understand the foundations upon which he based his explanations of the reasons behind the readings' variations, The research begins with an introduction to define the subject and its importance, followed by a biography of Abu Al-Fadl Al-Hariri's, and then a study of his methodology in providing evidence for the readings. The research emphasizes that the readings of the Companions and the script of the Quran, as well as the arabic language and its dialects are among the main foundations that Abu Al-Fadl Al-Hariri relied upon when providing evidence for the readings, The research also confirms that the evidence of Abu Al-Fadl Al-Hariri in explaining the proofs of readings were in alignment with the Explanations of reciters and interpreters.
Keywords: أبو الفضل الحريري; الاحتجاج; القراءات; توجيه; القرّاء